PERENCANAAN PERMINTAAN BAHAN BAKU DAN PENENTUAN UKURAN PEMESANAN (LOT SIZE) OPTIMAL DI GUDANG KIMIA MARUNDA - Ranran Rohani; Babay Jutika Cahyana (Universitas Bunda Mulia, 2022)
This research was conducted on companies that store and distribute chemical raw materials (sodium sulfate) to industrial companies. The problem that occurs is that the company does not have a medium-term raw material demand plan to determine the optimal order size to suppliers as storage in the warehouse. Given that ordering is also important to note because it has an impact on the total cost of inventory from ordering costs and holding costs. The purpose of this study is to forecast to find out the demand for raw materials in the future so that the company has an estimate for planning future demand for raw materials and calculates several ordering methods (lot size) to get the optimal order size.Solving problems using forecasting methods (Moving Average, Weight Moving Average, Exponential Smooth), and lot size methods (Economic Order Quantity, Period Order Quantity, Least Unit Cost, Part Period Balancing). The results of the analysis, forecasting to determine the demand for raw materials for the next year using the Exponential Smooth method because it has the smallest MAD MSE MAPE value, and the ordering lot size using the Part Period Balancing method because it has the minimum total inventory cost of Rp. 14,128,706,027 or 23.5% more efficient than the usual ordering used by companies.